2003
DOI: 10.1029/2001jb000187
|View full text |Cite
|
Sign up to set email alerts
|

Seismic velocity anomalies beneath SE Brazil from P and S wave travel time inversions

Abstract: [1] We present the result from teleseismic travel time inversions for P and S wave data mainly recorded at portable broadband stations in SE Brazil. The stations were deployed at 45 sites within an area 1000 Â 1700 km during the years 1992-1999. More than 10,000 relative P and S wave arrival times, including core phases, were obtained from the waveforms using a new coherence functional. These P and S relative phase times are independently inverted for slowness perturbations, earthquake relocations, and station… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
88
0
30

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(130 citation statements)
references
References 39 publications
12
88
0
30
Order By: Relevance
“…Moreover, neither a geoid anomaly nor a surface expression of the Tristan da Cunha thermal anomaly has been recognized in this region (Molina and Ussami, 1999;Ernesto et al, 2002). Schimmel et al (2003) argued that low velocities of seismic waves at lithospheric depths in South America characterize all the areas with late Cretaceous post-rift alkaline intrusions. If this is correct, the late Cretaceous alkaline intrusions may extend to the Apoyaya complex (NW Bolivia; Schultz et al, 2004) through the regions of Goiás and Mato Grosso in Brazil (Sousa et al, 2005) and southeastern Bolivia (Comin-Chiaramonti et al, 2005b).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, neither a geoid anomaly nor a surface expression of the Tristan da Cunha thermal anomaly has been recognized in this region (Molina and Ussami, 1999;Ernesto et al, 2002). Schimmel et al (2003) argued that low velocities of seismic waves at lithospheric depths in South America characterize all the areas with late Cretaceous post-rift alkaline intrusions. If this is correct, the late Cretaceous alkaline intrusions may extend to the Apoyaya complex (NW Bolivia; Schultz et al, 2004) through the regions of Goiás and Mato Grosso in Brazil (Sousa et al, 2005) and southeastern Bolivia (Comin-Chiaramonti et al, 2005b).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Van Decar et al (1995) and Schimmel et al (2003) identified a "cylindric" low-velocity volume in the upper mantle and mantle transition zone beneath the northeastern Paraná basin (Iporá late Cretaceous magmatic province -San Francisco craton), and this was interpreted as a thermal anomaly corresponding to the "fossil" Tristan da Cunha plume that had moved with the lithospheric plate. In contrast, Liu et al (2003) suggested that the thermal anomaly does not extend into the mantle transition zone or, alternatively, that the observed anomaly is not primarily thermal, but dominantly compositional in origin (e.g., "veined mantle").…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Nos trabalhos anteriores de tomografia sísmica regional (VanDecar et al, 1995;Schimmel et al, 2003) A tl a n ti c O c e a n Amazon ian Craton…”
Section: Principais Estudos Anterioresunclassified
“…Este movimento está relacionado ao fluxo astenosférico, o qual, estaria, segundo Assumpção et al (2006), desviado localmente pela topografia da interface litosfera/astenosfera (quilha) sob o Cráton do São Francisco. Schimmel et al (2003) observaram anomalias de alta velocidade para ondas P e S no manto superior abaixo da porção oeste da Bacia do Paraná. Esta anomalia poderia indicar a presença de um núcleo cratônico (Bloco Paraná - Cordani et al, 1984).…”
Section: Principais Estudos Anterioresunclassified
See 1 more Smart Citation